KARAKTER PESERTA DIDIK DENGAN PENDIDIKAN KEWARGANEGARAAN - Mae Afriliani; Dinie Anggraeni Dewi (Jurnal Ilmu Pendidikan Ahlussunnah, 2021)
Civic education is one of the subjects that gives learners insight into critical, rational, creative, responsible thinking and interacting with other nations. Character education is one of the requirements for joint responsibility, especially for the school, which is the principal thing in character education. The problem problem which the author will discuss in this research is whether the character of the learner is compatible with the education of citizenship? The purpose of this study is to know that citizenship education in the country of Indonesia has already applied its full character education. The study method in this article uses a descriptive and angket method, resulting from the study that the character education of leaners in civics is unfinished.